Structure and physics of viruses : an integrated textbook - Mateu, Mauricio G. (Subcellular Biochemistry, 2013)
Structural Virology is today an all-important scientific discipline that permeates most other virological disciplines. The application of physical and physicochemical techniques has led to the determination of the high-resolution molecular structures of many viruses. The interplay of this approach with biochemical and biological approaches has allowed the elucidation of the structural basis of viral function in unprecedented detail. In addition, in the last years theoretical and experimental physicists have begun to tackle a fundamental physics-based approach to study different aspects of the architecture, self-assembly and material properties of virus particles. A new term, Physical Virology, has recently been coined to encompass these and related studies. This approach is beginning to merge with long-standing structural virology approaches to provide a renewed and richer view on viruses, as well as further advances in the fight against viral disease and the applications of viruses in biotechnology and nanotechnology. Structure and Physics of Viruses is an interdisciplinary textbook in which the rapidly expanding fields of structural and physical virology are dealt with in an integrated way. The authors have attempted to write a book basic enough to be useful to students, as well as advanced and current enough to be useful to senior scientists. This book is aimed first at M.Sc. students, Ph.D. students and postdoctoral researchers with a university degree in biology, chemistry, physics or related sciences who share an interest or are actually working on viruses. It is aimed also at providing an updated account of many important concepts, techniques, studies and applications in structural and physical virology for established scientists working on viruses, irrespective of their physical, chemical or biological background and their field of expertise.